Lyophilized microculture susceptibility test for ketoconazole, miconazole, clotrimazole, and griseofulvin against dermatophytes. - Granade, T C (1983)
A lyophilized microculture antimycotic susceptibility testing system for ketoconazole, miconazole, griseofulvin, and clotrimazole is described. Microculture plates were loaded with 100 microliters of medium and 10 microliters of appropriate concentrations of the four antimycotics and were lyophilized to complete dryness. The lyophilized plates were stored at -70 degrees C or 4 degrees C or in a desiccator at 25 degrees C. Samples from each storage condition were rehydrated at 1, 2, 3, 4, 5, 6, 8, 10, and 12 months and inoculated with Trichophyton mentagrophytes (Robin) Blanchard ATCC 18748. All of the minimal inhibitory concentrations (MICs) generated from the lyophilized microcultures were within one experimental dilution of MICs derived from fresh microcultures. The ability of reconstituted lyophilized microcultures to consistently produce MICs comparable to MICs derived from fresh microcultures was characterized. Nine dermatophyte isolates were tested five times each over a 70-day period. The MICs derived were reproducible and comparable to MICs determined by freshly prepared microculture tests. Lyophilization of freshly prepared antimycotic-containing microcultures does not alter the MIC resolution of the testing system and provides an effective method of storage of prepared antimycotic tests for ketoconazole, miconazole, clotrimazole, and griseofulvin.